2020
DOI: 10.1111/trf.16099
|View full text |Cite
|
Sign up to set email alerts
|

Donation related fears predict vasovagal reactions and donor attrition among high school donors

Abstract: Background This longitudinal study of high school whole blood donors examined relationships among donation‐related fears assessed prior to donation, vasovagal reactions to donation, and the proportion of donors who attempted another donation over the subsequent 60 weeks. Study Design and Methods Data regarding vasovagal reactions and attempted donation were obtained from donor records of 530 female and 342 male high school donors who answered questions about five types of fear (ie, of blood draw, needles, seei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
(33 reference statements)
4
18
0
Order By: Relevance
“…Other papers reaffirm the relationship between fear and adverse reactions 16,18 and concur with the present data in showing that it is possible to bolster psychological outcomes with only a brief and inexpensive fear-related intervention. However, this study had a number of limitations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Other papers reaffirm the relationship between fear and adverse reactions 16,18 and concur with the present data in showing that it is possible to bolster psychological outcomes with only a brief and inexpensive fear-related intervention. However, this study had a number of limitations.…”
Section: Discussionsupporting
confidence: 87%
“…8 For example, fear, especially fear of the blood draw, is a key predictor of VVRs though it is not routinely assessed. [9][10][11][12][13][14][15][16] Importantly, more than half of firsttime donors and more than one-third of experienced donors report fear of the blood draw at the donation clinic. 17 This fear can be assessed quickly and reliably in donor centers by simply asking the donor to rate how fearful they are of having blood taken from their arm on a Likert-type scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…about future donations) and donation-related fear (i.e., concerns about stimuli in the immediate donation environment, such as needles and blood) have lower future donation intentions and a decreased likelihood of actual donation behavior. [1][2][3][4][5][6][7] Whereas anxious and fearful reactions to donation procedures and related stimuli likely dissuade many people from ever choosing to give blood, for a variety of reasons, many others decide to donate despite their concerns. In fact, a recent survey 8 indicated that 71.8% of first-time blood donors reported a fear of having blood drawn, and similarly high proportions reported a fear of blood donation needles (71.1%), feeling pain while donating (72.5%), and feeling faint or lightheaded while donating (67.6%).…”
mentioning
confidence: 99%
“…The reaction may have impact beyond the medical harm, though. Significantly, the donor who has a reaction is less likely to return, to become that “repeat donor” that all blood collectors covet 2‐4 . Additionally, a donor who has a visible reaction that requires care can alarm those already donating or those waiting to donate, potentially leading to increased fainting episodes simply due to the power of suggestion (the domino effect).…”
mentioning
confidence: 99%